A Visual Evaluation Framework for In-Home Physical Evaluation - Khan, Naimul Mefraz; Lin, Steve; Guan, Ling; Guo, Baining (International Symposium on Multimedia (ISM), 2014)
We propose a novel method for in-home physical rehabilitation, where a user can visually evaluate his/her performance compared to that of an expert. Normalized joint coordinates extracted from the Kinect skeleton are used as features. A novel Incremental Dynamic Time Warping (IDTW) algorithm is used to align the user and expert sequences. IDTW extends the classic DTW by providing accurate comparison between incomplete (the user's) and complete (the expert's) sequences while significantly reducing the computational time. Instead of providing a single measurement, the proposed method maps the IDTW measurements to a color-coded skeleton frame. Different colors on the limbs provide the user with an easy-to-interpret evaluation of how he or she is performing. Preliminary analysis involving different users and exercises and comparisons against the classic DTW algorithm show the effectiveness of the proposed method.